1985
DOI: 10.1677/joe.0.1040415
|View full text |Cite
|
Sign up to set email alerts
|

Parachlorophenylalanine blocks the spontaneous pro-oestrous surge of prolactin as well as LH and affects the secretion of oestradiol-17β

Abstract: The effect of the 5-hydroxytryptamine synthesis inhibitor, parachlorophenylalanine (PCPA), on the spontaneous, pro-oestrous surges of prolactin and LH was investigated in conscious female rats implanted with an intra-atrial cannula. The LH surge was blocked in all animals treated with PCPA, but the prolactin surge was blocked in six out of ten animals and unaffected in four out of ten animals. There was a significant correlation between the plasma concentrations of prolactin and oestradiol-17 beta, surges of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…1). It has been shown by others that pCPA can block the pro-oestrous surges of prolactin and LH (Walker & Wilson, 1983;Horn & Fink, 1985) and also the surges of both hormones induced by administration of oestrogen or oestrogen plus progest¬ erone to chronically ovariectomized rats (Caligaris & Taleisnik, 1974;Coen & McKinnon, 1979;Iyengar & Rabii, 1983;Walker & Wilson, 1983;Meyer &Eadens, 1985). This effect of pCPA seems to be mediated by serotonin depletion or by the disappearance of the daily rhythm of serotonin (Walker & Wilson, 1983;Walker, 1984).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…1). It has been shown by others that pCPA can block the pro-oestrous surges of prolactin and LH (Walker & Wilson, 1983;Horn & Fink, 1985) and also the surges of both hormones induced by administration of oestrogen or oestrogen plus progest¬ erone to chronically ovariectomized rats (Caligaris & Taleisnik, 1974;Coen & McKinnon, 1979;Iyengar & Rabii, 1983;Walker & Wilson, 1983;Meyer &Eadens, 1985). This effect of pCPA seems to be mediated by serotonin depletion or by the disappearance of the daily rhythm of serotonin (Walker & Wilson, 1983;Walker, 1984).…”
Section: Discussionmentioning
confidence: 95%
“…Never¬ theless, Horn & Fink (1985) found that administration of pCPA decreased oestradiol production by the ovar¬ ies in pro-oestrous rats, which could explain, at least partially, the inhibitory action of this drug on prooestrous prolactin release, which is oestrogen depend¬ ent. This possibility, however, may be discounted because pCPA was equally effective in inhibiting the oestrogen-induced prolactin surge in the rats ovari¬ ectomized on dioestrous day 2 (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(1, [12][13][14][15]. While some earlier studies suggested that 5-HT inhibits LH release, the majority of data suggest that 5-HT eously ovulating mammals is triggered by a spontaneous surge of LH releasing hormone (LHRH ) which, in the rat, plays a major role in stimulation of the LH surge (14)(15)(16)(17)(18)(19). The apparent discrepancy between 5-HT inhibition and 5-HT occurs on the afternoon of pro-oestrus.…”
mentioning
confidence: 99%
“…data]. Re cently Horn and Fink [11] also demonstrated that low blood levels of estrogen stimulate only a prolactin surge, whereas higher levels of the steroid are required to induce both, a prolactin and LH surge. The failure of the estrogen treatment used in the present study to induce LH surges is not due to a traumatization of the hypothalamus, be cause estrogens, when given subcutaneously, were able to induce LH surge in push-pull-cannula-implanted ani mals [3].…”
Section: Discussionmentioning
confidence: 99%